2021
DOI: 10.18535/ijsrm/v9i08.em03
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Foreign Direct Investment on Economic Growth of India

Abstract: International capital flows have a significant role for growth and development of recipient countries by providing necessary capital, resources and technology. One aspect of such international investment is Foreign Direct Investment (FDI) which has become an important source of external finance since they are considered as more stable and prominent source of capital inflows. The present study has been conducted to evaluate long-run and short-run impact of FDI on economic growth of India. Gross Domestic Product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
0
0
Order By: Relevance
“…The impact between international presence and local economic development is undeniable. Studies have shown that internationalization, particularly through foreign direct investment, significantly contributes to regional economic growth, as seen in the case of India [1]. However, the mixing of foreign and local economies is not without challenges.…”
Section: Introductionmentioning
confidence: 99%
“…The impact between international presence and local economic development is undeniable. Studies have shown that internationalization, particularly through foreign direct investment, significantly contributes to regional economic growth, as seen in the case of India [1]. However, the mixing of foreign and local economies is not without challenges.…”
Section: Introductionmentioning
confidence: 99%